2016
DOI: 10.1097/sap.0000000000000751
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reconstructive Outcomes in Breast Cancer Patients With Preexisting Subpectoral Implants

Abstract: Implant-sparing mastectomy with delayed implant exchange in patients with preexisting subpectoral implants is safe and has fewer complications compared to tissue expander placement. There was no difference noted in the final volume of implant placed, time interval for final implant placement, or tumor margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Patients can then be reassured that having a breast augmentation does not prevent them from getting properly screened and appropriately treated for breast cancer 19 . In addition, a prior study has shown that implant-sparing mastectomies with delayed implant exchange in patients with pre-existing subpectoral implants are safe, have fewer complications, and have similar tumor margins when compared with tissue expander placement 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients can then be reassured that having a breast augmentation does not prevent them from getting properly screened and appropriately treated for breast cancer 19 . In addition, a prior study has shown that implant-sparing mastectomies with delayed implant exchange in patients with pre-existing subpectoral implants are safe, have fewer complications, and have similar tumor margins when compared with tissue expander placement 20 …”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, a prior study has shown that implant-sparing mastectomies with delayed implant exchange in patients with pre-existing subpectoral implants are safe, have fewer complications, and have similar tumor margins when compared with tissue expander placement. 20 The study was limited by being observational and retrospective in nature. Because only the NISM group had a prior breast augmentation, the comparison of the groups may be skewed.…”
Section: Discussionmentioning
confidence: 99%